2007
DOI: 10.1371/journal.pone.0000664
|View full text |Cite
|
Sign up to set email alerts
|

HLA-A Confers an HLA-DRB1 Independent Influence on the Risk of Multiple Sclerosis

Abstract: A recent high-density linkage screen confirmed that the HLA complex contains the strongest genetic factor for the risk of multiple sclerosis (MS). In parallel, a linkage disequilibrium analysis using 650 single nucleotide polymorphisms (SNP) markers of the HLA complex mapped the entire genetic effect to the HLA-DR-DQ subregion, reflected by the well-established risk haplotype HLA-DRB1*15,DQB1*06. Contrary to this, in a cohort of 1,084 MS patients and 1,347 controls, we show that the HLA-A gene confers an HLA-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
112
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 19 publications
11
112
0
2
Order By: Relevance
“…The frequency of MOG-142L and HLA-A*02-positive individuals was significantly lower in cases than in controls, confirming the previously reported protective effect, 9,10,12,13 whereas the association with Cw*05 was not significant. To eliminate the possible confounding effect of linkage disequilibrium (LD) with HLA-DRB1*15, we performed the same analysis in DRB1*15-negative individuals.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The frequency of MOG-142L and HLA-A*02-positive individuals was significantly lower in cases than in controls, confirming the previously reported protective effect, 9,10,12,13 whereas the association with Cw*05 was not significant. To eliminate the possible confounding effect of linkage disequilibrium (LD) with HLA-DRB1*15, we performed the same analysis in DRB1*15-negative individuals.…”
Section: Resultssupporting
confidence: 86%
“…8 Conversely, other studies have detected the effect at least of one class I genetic factor independently of HLA-DRB1. Brynedal et al 9 confirmed in a Nordic cohort of 1084 MS patients and 1347 controls the results of a previous study performed in a smaller Swedish panel, 10 showing that HLA-A*02 is negatively associated with MS (OR ¼ 0.63, P ¼ 7 Â 10 À12 ). Yeo et al 11 analyzed over 1600 UK MS patients and 3600 controls and found that HLA-Cw*05 exerts an MS-protective effect (OR ¼ 0.49, 95% confidence intervals, CI ¼ 0.34-0.69, P ¼ 3.3 Â 10 À5 ) after excluding all individuals carrying DRB1 alleles associated with MS.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Furthermore, HLA class II-independent associations with HLA-A and -B have also been reported with other AIDs. In particular, HLA-A has been implicated in multiple sclerosis [34][35][36] and juvenile idiopathic arthritis, 37,38 whereas HLA-B is a well-known risk factor in ankylosing spondylitis 39 and has been implicated in systemic lupus erythematosus. 40 This raises the possibility that these genes represent susceptibility loci that are involved in common, autoimmune processes.…”
Section: Confirmation Of Mhc Class I Associationsmentioning
confidence: 99%
“…Recent genetic studies strongly advocate an independent association between specific major histocompatibility complex (MHC) class I alleles and MS [8]. The exact contribution of CD8 T cells in the pathogenesis of MS remains ambivalent as the HLA-AÃ0301 allele is reported to increase susceptibility [9,10], whereas the HLA-AÃ0201 allele confers protection from the disease [4,11]. This review discusses the recent advances regarding functionally distinct CD8 T cell subsets and their implication in the pathogenesis of MS.…”
Section: Introductionmentioning
confidence: 99%